2005
DOI: 10.1007/s00421-005-0073-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of menstrual phase on performance and recovery in intense intermittent activity

Abstract: Game sport and training require repeated high intensity bursts. This study examined differences between high intensity, intermittent work in two phases of the menstrual cycle. Six physically active young women (age 19-29) performed 10 6-s sprints on a cycle ergometer in both the mid-follicular (FP) (days 6-10) and late-luteal phases (LP) (days 20-24) of the menstrual cycle. Work, power, oxygen intake (VO2) parameters, and capillarized blood lactate were measured. Data are analyzed using the Friedman and Wilcox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 29 publications
4
42
0
1
Order By: Relevance
“…Mean peak whole blood lactate concentration did not change due to MCP, a finding which is consistent with previous investigations (Lynch and Nimmo 1998;Middleton and Wenger 2006). In addition, blood pH values were similar across MCPs.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Mean peak whole blood lactate concentration did not change due to MCP, a finding which is consistent with previous investigations (Lynch and Nimmo 1998;Middleton and Wenger 2006). In addition, blood pH values were similar across MCPs.…”
Section: Discussionsupporting
confidence: 91%
“…However, Harber et al (1998) reported that amenorrheic subjects had a different hypothalamic-pituitary thyroid axis profile compared with eumenorrheic-endurance athletes as indicated by lower thyroxine and triiodothyronine concentrations complicating any clear influences of reproductive hormones on recovery of PCr and thus on the recovery of sprinting (Bogdanis et al 1996). However, Middleton and Wenger (2006) did find higher work performed over a series of sprints during the luteal phase of the cycle and associated this improvement with the positive influence of 17b-estradiol on PCr restoration. However, peak power or recovery of power was unaltered due to MCP as it was in the present study.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Harber, Petersen, and Chilibeck (1998) demonstrated that amenorrheic endurance trained athletes have slower CP recovery rates, following plantar flexion exercises, than their eumenorrheic counterparts, suggesting an influence of ovarian hormone status on muscle phosphate recovery. Middelton and Wenger (2006) reported better total work after 10 times 6-second sprint in the cycle ergometer. These authors think that higher phosphocreatine (PCr) and adenosine triphosphate stores would explain the higher performance during LP.…”
Section: Discussionmentioning
confidence: 99%